The Assignment of Powers in an Open-ended European Union - Pierre Salmon (Center for Economic Studies and ifo Institute (CESifo), 2003)
A major characteristic of the European Union is its transitional or evolving nature, in particular with regard to the assignment of powers between the two main levels of government. More precisely, under current constitutional arrangements, this evolving nature takes the form of an integration process which tends to be monotonous, that is, which can only with great difficulty be reversed. The paper is mainly devoted to the explanation of how this comes about and what effects this has on other features of the process. As a concluding remark, however, it suggests that an additional criterion for judging – or an additional indicator for reading – proposed constitutional reforms can be derived from the analysis. This criterion or indicator should be of some value independently of the position adopted with regard to European integration.
Keywords: 330; European integration; European union; constitution; gradualism; transition